Promoting self-disclosure from prison inmates - Merits, Maynard A. (My University, 2017)
This study examined the effects of interviewer self-disclosure on the self-disclosure of 40 male prison inmates and 40 male university students. A four-point scale was used for rating the intimacy of selfdisclosure, the number of statements were counted for scoring the breadth of self-disclosure, and a stop watch was used to time the duration of self-disclosure. The three measures correlated highly with each others indicating all were good measures of self-disclosure. The self-disclosure reciprocity effect was demonstrated with both prison inmates and university students. It was also found that overall, prison inmates self-disclosed significantly less < .05) than university students. The personality variables of extroversion and neuroticism, as measured by the Eysenck Personality Inventory, were also examined. Prison inmates were significantly lower than university students on extroversion < .001) and no different than university students on neuroticism. It was also found that extroversion was positively related to self-disclosure. However, neuroticism was not related to either self-disclosure or to extroversion.
Keywords: Self-disclosure; Prisoners Attitudes